Impact of sleep inertia on visual selective attention for rare targets and the influence of chronotype. (4th April 2017) - Ritchie, Hannah K.; Burke, Tina M.; Dear, Tristan B.; Mchill, Andrew W.; Axelsson, John; Wright, Kenneth P.
Summary: Sleep inertia is affected by circadian phase, with worse performance upon awakening from sleep during the biological night than biological day. Visual search/selective visual attention performance is known to be sensitive to sleep inertia and circadian phase. Individual differences exist in the circadian timing of habitual wake time, which may contribute to individual differences in sleep inertia. Because later chronotypes awaken at an earlier circadian phase, we hypothesized that later chronotypes would have worse visual search performance during sleep inertia than earlier chronotypes if awakened at habitual wake time. We analysed performance from 18 healthy participants [five females (22.1 ± 3.7 years; mean ± SD)] at ~1, 10, 20, 30, 40 and 60 min following electroencephalogram‐verified awakening from an 8 h in‐laboratory sleep opportunity. Cognitive throughput and reaction times of correct responses were impaired by sleep inertia and took ~10–30 min to improve after awakening. Regardless whether chronotype was defined by dim light melatonin onset or mid‐sleep clock hour on free days, derived from the Munich ChronoType Questionnaire, the duration of sleep inertia for cognitive throughput and reaction times was longer for later chronotypes ( n  = 7) compared with earlier chronotypes ( n  = 7). Specifically, performance for earlier chronotypes showed significant improvement within ~10–20 min after awakening, whereas performance for later chronotypes took ~30 min or longer to show significant improvement ( P  < 0.05). Findings have implications for decision making immediately upon awakening from sleep, and are consistent with circadian theory suggesting that sleep inertia contributes to longer‐lasting impairments in morning performance in later chronotypes.